Original paperHypersensitivity to major panallergens in a population of 120 patients - Nucera, Eleonora; Mezzacappa, Simona; Aruanno, Arianna; Pecora, Valentina; Rizzi, Angela; Ricci, Anna Giulia; Ferraironi, Manuela; Buonomo, Alessandro; Schiavino, Domenico (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: Lipid transfer proteins (LTP), profilin and PR-10 are the most important panallergens in central and southern Italy. Lipid transfer proteins are stable molecules, predominantly present in the fruit peel, which can induce systemic symptoms after ingestion of vegetables. Profilin and PR-10 are randomly distributed in the pulp and peel. Both are labile proteins and usually determine reactions restricted to the oral cavity. Panallergens-specific IgE may cross-react with homologues from different plant sources, due to their conserved structure. Aim: To assess the pattern of sensitization to panallergens and the correlation with the clinical history and the allergological evaluation of food and aeroallergens. Material and methods: One hundred and twenty patients with adverse reactions after vegetables ingestion underwent skin prick tests (SPT) with commercial extracts of plant-derived foods and inhalant allergens and commercial extracts of LTP, profilin and PR-10. Results: Many patients presented positive SPT with different plant-food allergens. We found that 76 patients were sensitized to LTP, 14 to profilin and 5 to PR-10. In the LTP-sensitized group, 64 (84%) patients suffered from systemic symptoms while the patients sensitized only to profilin referred the oral allergy syndrome. Conclusions : This study shows a high rate of sensitization to LTP in our population according to the literature about food allergy in our geographical area and confirms the literature data about the symptoms referred by patients with sensitization to panallergens. Panallergens should be considered as clinically relevant food allergens.